2016
DOI: 10.1016/j.chemosphere.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

DDT exposure of frogs: A case study from Limpopo Province, South Africa

Abstract: Highlights Contaminants is suspected to play a part in amphibian declines worldwide  No POPs data in frogs from areas where DDT is used for malaria control  Quantifiable DDT was found in frog fat from an area where DDT is used  No testicular oocytes were found in any frog  Significant asymmetric testicular morphology in frogs from the sprayed area AbstractAmphibians are globally under pressure with environmental contaminants contributing to this. Despite caution aired more than 80 years ago of threats pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 54 publications
0
16
1
Order By: Relevance
“…Different EDCs also elicit an effect through different modes of actions. The majority of ED related studies in South Africa have investigated disruption of reproductive systems ( Barnhoorn et al , 2010 ; Kruger et al , 2013 ; Arukwe et al , 2016 ; Viljoen et al , 2016 ; Leusch et al , 2018 ) ( Table 1 ) and when EDCs elicit an effect on the reproductive system, the response (mode of action) can either be (anti-)oestrogenic or (anti-)androgenic ( Archer and Van Wyk, 2015 ).…”
Section: Endocrine Disrupting Effects Observed In South African Watermentioning
confidence: 99%
See 2 more Smart Citations
“…Different EDCs also elicit an effect through different modes of actions. The majority of ED related studies in South Africa have investigated disruption of reproductive systems ( Barnhoorn et al , 2010 ; Kruger et al , 2013 ; Arukwe et al , 2016 ; Viljoen et al , 2016 ; Leusch et al , 2018 ) ( Table 1 ) and when EDCs elicit an effect on the reproductive system, the response (mode of action) can either be (anti-)oestrogenic or (anti-)androgenic ( Archer and Van Wyk, 2015 ).…”
Section: Endocrine Disrupting Effects Observed In South African Watermentioning
confidence: 99%
“…Endocrine disrupting effects have also been observed in frog species. Viljoen et al (2016) reported on the asymmetric testicular morphology of frogs that naturally occur in dams and ponds in Limpopo where DDT is still sprayed for malaria control. This phenomenon was attributed to possible ED caused by DDT ( Table 1 ).…”
Section: Endocrine Disrupting Effects Observed In South African Watermentioning
confidence: 99%
See 1 more Smart Citation
“…None of the frogs analysed had accumulated DDT or metabolite concentrations above limit of detection (0.01 μg/g), except one individual which had 0.054 μg/g wm p,p-DDE. Viljoen et al (2016) measured DDT in X. laevis and X. muelleri fat bodies in an area sprayed with DDT for MVC through means of IRS in the Limpopo Province of South Africa. All DDT metabolites detected showed higher accumulation at sprayed sites compared to reference sites.…”
Section: Organochlorinesmentioning
confidence: 99%
“…Despite widespread discontinuation of DDT spraying many countries still regularly use DDT (See van den Berg 2009). Concentrations of DDT have been detected in fish, water and sediment samples across a number of different systems (Gerber et al 2016;Viljoen et al 2016;Wolmarans et al 2018). However, there is disturbingly little data available on the myriad potential effects of DDT on the ecology of freshwater systems.…”
Section: Introductionmentioning
confidence: 99%